Le pseudonyme dans la littérature algérienne brouillage de pistes ou fantaisie... - Mohamed BOUDJADJA, (مجلة الآداب و العلوم الإجتماعية, 2013)
Abstract Long considered a marginal practice, the literary pseudonym has been little studied. Yet, many works have been published under a wrong name often confusing readers. Current practices in literature, masks and pseudonyms are perceived as synonymous with freedom, protection, or a change in kind. But what exactly does this interference of the tracks? Is this proof of imagination or a poetic touch? Is it a literary hoax or a hint of authenticity? This article attempts to examine the reasons and functions of this practice auctorielle in Algerian literature; it also deals with this aspect of writing whose ultimate aims, though unavowed, would still be political and poetic.